A Review on Measurement Methods for Machining Induced Residual Stress - Kushendarsyah Saptaji; Siti Nur Afiqah; Raden Dadan Ramdan (Faculty of Engineering and Technology, Sampoerna University, 2019)
The chip formation in mechanical machining / cutting process involves thermal loading and mechanical loading in the form of large plastic deformations, high strain, strain rates and high temperatures in the cutting zone. These loadings usually induce plastic deformation in the form of residual stresses in the surface and sub-surface of the machined workpiece. Residual stress issue is essential to be studied in order to control the quality and fatigue life of a component or part produced by machining process. Therefore, the magnitude and depth of the residual stresses into the workpiece sub-surface is important and necessary to be measured. The objective of this paper is to discuss various study on the effects of machining parameters on residual stress and residual stress measurement methods for machined workpiece namely non-destructive, semi-destructive and destructive methods. In addition, the effect of machining process into the metallurgical conditions of the workpiece in the form of microstructural changes is also discussed.